Correlation of Serum Levels of IL-33, IL-37, Soluble Form of Vascular Endothelial Growth Factor Receptor 2 (VEGFR2), and Circulatory Frequency of VEGFR2-expressing Cells with Multiple Sclerosis Severity - Ebrahim Kouchaki; Omid Reza Tamtaji; Ehsan Dadgostar; Mohammad Karami; Hassan Nikoueinejad; Hossein Akbari (Iranian Journal of Allergy, Asthma and Immunology, 2017)
IL-33 and IL-37 (new cytokines of IL-1 family), soluble form of vascular endothelial growth factor receptor-2 (sVEGFR2) as well as membranous expression of VEGFR2 have some key roles in the pathogenesis of autoimmune and inflammatory diseases. The aim of this study was to correlate circulatory changes of these factors with the severity of multiple sclerosis (MS) as an autoimmune and inflammatory disease. Our case-control study was performed on 84 patients with MS and 75 healthy subjects. The serum levels of IL-33, IL-37 and sVEGFR2 in the peripheral blood samples of all participants were measured by enzyme-linked immune sorbent assay (ELISA). Flow cytometry was used to analyze the circulatory number of VEGFR2-expressing cells. The severity of MS was evaluated using the expanded disability status scale (EDSS). Finally, we evaluated the correlation between serum levels of those factors with disease severity. Our findings showed that the serum level of IL-33, IL-37, sVEGFR2 and the circulatory number of VEGFR2-expressing cells were increased in patients with MS compared to healthy subjects (p<0.0001). Also, there was a significant correlation between serum levels of these 3 factors with disease severity according to EDSS. Our study showed that the serum levels of IL-33, IL-37 and sVEGFR2 may be important prognostic biomarkers of MS.